Imperium Japonicum Per Sexaginta Et Sex Regiones Digestum Atque Ex Ipsorum Japnensium Mappis Descriptum Per Matthaeum Seutter, S. Caes. Et Reg. Cathol. Majg. Geogr. Augustan. - Seutter, Matthaeus, 1678-1756 (Homann Erben (Firm), 1744)
18th century Copper engraving handcolored with watercolor. Full color. Relief shown pictorially. Includes compass rose in center at top. Printed above top border: "Imperium Japonicum Per Sexaginta Et Sex Regiones Digestum Atque Ex Ipsorum Japnensium Mappis Descriptum Per Matthaeum Seutter, S. Caes. Et Reg. Cathol. Majg. Geogr. Augustan." Printed in upper left beneath border: Cum Gratia et Privil. S. R. I. Vicariatg. in partibg. Rheni Sveviae, et Juris Franconici." Printed in center of bottom in cartouche is a description of European encounters with Japan: "Particulam hanc, quae sinum oppidi Nangasacki exhibit, descripsi ex inedita mappa in qua Batavus quidam insulam Firando (ubi haec nation sedem fibi elegit)…" Printed in cartouche in lower left corner: "Eoi regina maris, quae prima citatos Conspicis a rubro gurgite Solis equos, Et bis tricenas late digesta per oras, Sic populis gaudes inspicienda dari. Fixerunt Batavi sedem hic. Num denique credas, Hos quidquam intactum posse lataere Viros?" Printed at top is a scale for German miles. Written in ink in upper right corner above border: "96 [crossed out]. 87." Written in pencil in upper right corner above border: "87." Depicts Japan with places shown throughout using both Japanese characters and their Latinized place names. Shows Japan as divided into "Koesioe," "Sikokf, and "Nipon." In the lower right is an inset map of Nagasaki showing the sounding depths of the coastline of the area near Nagasaki on the island of Kioesioe. Various shields with different designs are depicted within the inset map. Of note to the northeast, the mythical land of Yesso or "Jedso" is shown. Shows the major towns, roads, lakes and mountains. Above the center cartouche classical figures and an angel recline while below Japanese men are shown at work. Georg Mathaus Seutter (1678-1756) was a map publisher and cartographer from Nuremberg who set up shop in Augsburg. After an apprenticeship with J. B. Homann in 1697, he began working in Augsburg and was eventually appointed Geographer to Imperial Court. Throughout his lifetime, he competed with his old mentor and worked closely with his son-in-law to put out a collection of town plans. His works include "Atlas Germanicus" (c. 1720), "Atlas Geographicus" (1725), "Atlas Novus" (1728), "Grosser Atlas" (c. 1735), "Atlas novus sive tabulae geographicae totius orbis" (c. 1741), and "Atlas Minor" (1744). After his death, his son, Albrecht Karl, continued the business (Moreland and Bannister, 87-8; Tooley, "Dictionary of Mapmakers," 557). The land of "Iesso" or "Yezo" was an island allegedly lying north of Japan. Later identified as Hokkaido, explorers in the seventeenth century were unsure of its nature. The Russians attempted to discern whether Yezo was indeed an island or part of Asia with a number of expeditions in the seventeenth century. Under the reign of Peter the Great, the explorers were able to chart Russia's Kamchatka Peninsula and the Kurile Islands. In the 1780s, a French expedition sailed between Yezo and Korea, and then, through the Kuriles (Tooley and Bricker, 130). Source(s): Moreland, Carl and David Bannister. "Antique Maps: A Collector's Handbook." New York: Longman Group, Ltd., 1983. Tooley, Ronald Vere. "Tooley's Dictionary of Mapmakers." Hertfordshire: Map Collector Publications Limited, 1979. Tooley, Ronald Vere and Charles Bricker. "Landmarks of Mapmaking: An Illustrated Survey of Maps and Mapmakers." Amsterdam: Elsevier, 1968.